Metabolic Disequilibrium: A Review in the Indication of Soil Ecosystem Insulted with Xenobiotics - Ebulue, M. M. (Bumi Publikasi Nusantara, 2023)
The establishment of metabolic equilibrium in the soil ecosystem the following insolation is a prerogative of soil communities. These communities comprise microorganisms of diverse species and populations. The hydrocarbon-degrading communities (i.e., hydocarbonclastics) are found in petroleum or crude oil, polluting soil ecosystems. Others, the non-petroleum degrading microbial communities are diverse in nature and occur in soil, water, and air ecosystems. In the event of oil pollution with inherent disequilibrium in the ecosystem, the prejudicial nature of the petroleum will reduce the biomass of the non-hydrocarbon degrading organisms. Consequently, there will be an insurgence of the hydrocarbon degraders to metabolize the xenobiotics and bring the affected ecosystem to a balance and equilibrium. This is the hallmark of the entire ecosystem function. For other non-petroleum degraders in an ecosystem insolted with xenobiotics except petroleum, they will consolidate in their degradative activity to bring the affected ecosystem to a balance and equilibrium. Overall, the insolation of an ecosystem with any xenobiotics results in a disequilibrium, in which the indigenous microbial communities through their metabolic activities will bring the affected ecosystem to a balance and equilibrium.